Sales of products and development of financial results - Djumabaeva Nurzada To'rebek qizi (Periodica Journal, 2023)
The sales of products play a vital role in the overall financial performance and success of a business. This scientific article aims to explore the intricate relationship between sales and financial results, shedding light on the key factors that influence business success. By understanding these factors, organizations can make informed decisions to optimize their sales strategies and enhance their financial outcomes. The study draws upon relevant literature, statistical analysis, and real-world examples to provide a comprehensive overview of the topic.
Keywords: Products; Sales; Financial results